Structural and magnetic properties of hydrothermally synthesized Bi-substituted Ni–Co nanosized spinel ferrites. Issue 4 (15th February 2022) - Alqarni, Ameerah N.; Almessiere, M.A.; Güner, S.; Sertkol, M.; Shirsath, Sagar E.; Tashkandi, N.; Baykal, A.
Abstract: In this study, the structural, morphological, and magnetic properties of hydrothermally synthesized Co 0.5 Ni 0.5 Bi x Fe 2-x O 4 (x=0.00–0.10) nanosized spinel ferrites, (CoNiBiFO (x=0.00–0.10) NSFs), were investigated. The formation of CoNiBiFO NSFs phase was confirmed by X-ray diffraction (XRD) . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the morphology of the NSFs . Magnetization revealed that undoped Co 0.5 Ni 0.5 Fe 2 O 4 and Co 0.5 Ni 0.5 Bi x Fe 2-x O 4 NSFs (except with x = 0.04) exhibit ferrimagnetic magnetism at 300 K. Only the hysteresis loops recorded from Co 0.5 Ni 0.5 Bi 0.04 Fe 1.96 O 4 NSFs have superparamagnetic characteristics. Mixed Co 0.5 Ni 0.5 Fe 2 O 4 NSFs have maximum remnant magnetization ( M r ) of 23.5 emu/g, maximum saturation magnetization ( M S ) of 63.38 emu/g, and maximum magneton number ( n B ) 2.66 μB . However, Co 0.5 Ni 0.5 Bi 0.04 Fe 1.96 O 4 NSFs have minimum M S of 28.25 emu/g and minimum n B as 1.22 μB among Bi 3+ doped and undoped samples. The coercivity ( H C ) of undoped Co 0.5 Ni 0.5 Fe 2 O 4 NSFs is 656 Oe. However, the Bi 3+ ion-doped samples have a wide range of H C values between 101 Oe and 1038 Oe. The squareness ratios are in the range of 0.092–0.418 and multi-domain structure is assigned for all types of samples. The measured positive exchange bias ( H E ) magnitudes are 268 Oe and 290 Oe, respectively. Hysteresis loops recorded at 10 K proved that the products are ferrimagnetic. These coercivities showed that all the samples are magnetically harder at low temperatures. Positive H E values of 165 Oe and 297 Oe were measured from the nanoparticles (NPs) with x = 0.08 and x = 0.10 at 10 K. The SQR of the Co 0.5 Ni 0.5 Bi 0.04 Fe 1.96 O 4 sample at 10 K is almost equal to the critical value of 0.5, and a single domain structure with uniaxial symmetry can be attributed for this sample. The other samples have SQRs in the range of 0.632–0.782 and multi-domain wall structure is assigned for them at 10 K.